Preparation, Optimization and Activity of Active Absorbent Synthesized from Oil Palm Ash for Flue Gas Desulfurization. - Noor, N.Mohamed; K, T Lee; Zainudin, N F; Mohamed, A R (2004)
Active absorbent for the removal of SO2 in flue gas from combustion system was prepared from oil palm ash,calcium hydroxide (Ca(OH)2) and calcium sulfate (CaSO4) using water hydration process. The effect of various absorbent preparation variables; hydration period, amount of oil palm ash and amount of CaSO4 used in the preparation mixture towards the BET (Brunauer-Emmett-Teller) specific surface area of the resulting absorbent were studied using Central Composite Design (CCD). The surface area of the absorbents obtained ranges from 18.7 to 147.2 m2/g.